Multi-Quartz Enhanced Photoacoustic Spectroscopy with Different Acoustic Microresonator Configurations - Zheng, Huadan; Yin, Xukun; Dong, Lei; Wu, Hongpeng; Liu, Xiaoli; Ma, Weiguang; Zhang, Lei; Yin, Wangbao; Jia, Suotang (Journal of Spectroscopy, 2015)
Acoustic microresonators were added to the recently developed multi-QTF based QEPAS spectrophone to enhance the signal amplitude. Two kinds of “on-beam” configurations were experimentally investigated in detail. The developed multi-QTF based “on-beam” spectrophone had a signal enhancement of 1.6 times compared with the traditional single QTF based “on-beam” spectrophone, with the approximate noise level. A normalized noise equivalent absorption coefficient (1σ) of 1.24 × 10−9 W·cm−1·Hz−1/2 was obtained for water vapor detection at atmospheric pressure.